2012
DOI: 10.1515/cclm.2011.811
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Dioleoylglycerol method for pancreatic lipase catalytic activity in serum

Abstract: Although further studies are required, the DODG method may be likely applicable as one candidate reference method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The method was based on determining the turbidity change of a triolein emulsion measured by a spectrophotometer at a fixed wavelength of λ = 340 nm (UV detection). A similar system designed to operate under the same wavelength using 1, 2-dioleoylglycerol as the substrate with a covariance of 2.2·10 −3 U/mL was described [ 19 ]. The spectrum used in our lab-made SIA system can be configured from λ = 350 to 1000 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was based on determining the turbidity change of a triolein emulsion measured by a spectrophotometer at a fixed wavelength of λ = 340 nm (UV detection). A similar system designed to operate under the same wavelength using 1, 2-dioleoylglycerol as the substrate with a covariance of 2.2·10 −3 U/mL was described [ 19 ]. The spectrum used in our lab-made SIA system can be configured from λ = 350 to 1000 nm.…”
Section: Resultsmentioning
confidence: 99%
“…An automatic system to determine lipase activity was developed using as a substrate 1,2-dioleoylglycerol. The lipase activity was measured from the increase in absorbance at 340 nm in a coupled enzymatic reaction [ 19 ]. A potentiometric FIA titration system for monitoring lipase activity was performed using a commercial CaLB enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The only (indirect) data related to the analytical specifi city of the proposed assay that can be derived from the study are those reported in the Iizuka's Table 3, in which seems to be evident that the DODG method displays similar specifi city of another commercial 1,2-diglyceride method (i.e., the intercept of the regression equation is close to zero), but different specifi city when compared with the 1,2-o -dilauryl-rac -glycero-3-glutaric acid (6 ′ -methylresorufi n) ester (DGGR) method (positive intercept) (23) . On the other hand, as already demonstrated for quite similar substrates (18,20) , a marked positive interference in samples collected after intravenous heparin administration was noted.…”
Section: Mauro Panteghinimentioning
confidence: 93%
“…Similarly, the Japanese Society of Clinical Chemistry (JSCC) became active in searching for a reference measurement procedure for HPL. The paper published in this issue of Clinical Chemistry and Laboratory Medicine represents the fi rst outcome of the work commissioned by JSCC (23) . The proposed substrate for HPL is the 1,2-dioleoylglycerol (DODG) and the increase of NADPH, after a complex reaction scheme using four auxiliary reactions, is spectrophotometrically recorded in the indicator reaction of the method.…”
Section: Mauro Panteghinimentioning
confidence: 99%
See 1 more Smart Citation